PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN PT. MITRA GALANG SEJAHTERA JAKARTA - Muhammad Yusuf Aditama; Muhammad Harri (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2022)
Purpose to analyze the effect of service quality and price on customer satisfaction PT. Mitra Galang Sejahtera Jakarta. The research method uses descriptive qualitative and quantitative analysis, the analytical model used is linear regression, simultaneous and partially. The research population is customer PT. Mitra Galang Sejahtera Jakarta who use telecommunication service. The result simultaneous, service quality and price have a significant effect on customer satisfaction at PT. Mitra Galang Sejahtera Jakarta. Partially service quality has a positive and significant effect on customer satisfaction, and partially price has a positive and significant effect on customer satisfaction